The Influence of Field Work Practices, Entrepreneurship Knowledge, and Family Environment on Entrepreneurial Interests Through Soft Skill (Universitas Negeri Semarang, 2022)
Interest in entrepreneurship will increase if it is supported by students' field work practices, entrepreneurial knowledge, family environment, and soft skills possessed by students. This study aims to determine the effect of field work practices, entrepreneurial knowledge, and family environment on the interest in entrepreneurship through the soft skills of students of SMK Negeri Kabupaten OKU Timur. The research population was all students of class XII Accounting at SMK Negeri Kabupaten OKU Timur as many as 297 students and the sample was taken using a proportional random sampling cluster technique, a sample of 161 respondents was obtained. Data collection techniques were carried out through questionnaires given to respondents directly through validity and reliability tests. The data analysis technique used linear regression with prerequisite test and path analysis. The results showed: (1) there was a positive and significant effect of field work practice on soft skills (28.09%), (2) there was a positive and significant influence on entrepreneurial knowledge on soft skills (4.12%), (3) there was an influence positive and significant family environment on soft skills (1.69%), (4) there is a positive and significant effect of field work practices on interest in entrepreneurship through soft skills (55.4%), (5) there is a positive and significant influence of entrepreneurial knowledge on interest in entrepreneurship through soft skills (22.1%), (6) there is a positive and significant influence of the family environment on interest in entrepreneurship through soft skills (8.6%), and (7) there is a positive and significant influence of soft skills on interest in entrepreneurship ( 43.03%). The conclusion of this study is that field work practices, entrepreneurship recruitment, and family environment affect students' interest in entrepreneurship through soft skills of students at SMK Negeri Kabupaten OKU Timur.